Xamanismo Uhtãpinõponã: princípios dos rituais de pajelanças e do ser pajé Tuyuka - Dutra, Israel Fontes (2010)
This dissertation focuses on shamanism Uhtãpinõponã: principles of shamanic rituals and rites of the Tuyuka shaman being. The Tuyuka people speaks a language that belongs to the oriental tukano linguistic family, and dwells in the upper rio Negro, AM, Brazil and Departamento de Vaupés, Colombia. The goal is to describe the historical-cosmological foundations of the shamanic rituals and of the shaman Tuyuka being. The group is part of a complex web of kinship that constitutes the indigenous peoples of Uaupés river, which came from the House of Emergency Ohkó Diawi, located at the low Uaupés river, in Brazil. The history of the Upper Rio Negro shows that the missionary action on indigenous communities in the decades from 1920 to 1980 led to the almost total destruction of their cultural and spiritual life. The shamans, (yaíwa and basera or kumuã), masters of traditional songs and dances (bayaroa), masters of the Jurupari rituals (mahsãkuła yaíwa), became enemies of various representatives of the Catholic Church, which tried to eradicate them, based on the thesis that the traditional festivals, the rituals of shamanism (yaiałe and kumuãłe) and the jurupari rites were evil and that if they destroyed them, the Indians would become children of God and no longer the children of devil. However, they failed to destroy the essence of cultural and spiritual life of the Tuyuka people, because in despite of this cruel story, there is a cultural and spiritual sense experienced by the Tuyuka shamans. To show this experience, we present the following research topics: the Tuyuka people and its shamanic rituals historical and cosmological principles; the Tuyuka shaman being and the means of transmission of the shamanic rituals. The research took into account the following theoretical and methodological aspects: 1. the study of Mircea Eliade on the mith issue, that points the "myths" as "True Stories" 2. The thinkings of George Balandier which highlights the dynamic character of social reality that is based on the dialectic of order and disorder